Unfinished Revolution: Haiti, Black Sovereignty and Power in the Nineteenth-Century Atlantic World - Salt, Karen (Liverpool University Press, 2018)
Unfinished Revolution is the first study to gather nineteenth-century representations and performances of Haitian sovereignty in the Atlantic world. In assembling this undiscovered archive of black power, this book offers compelling evidence of the ways that sovereignty and blackness intersect with unstable processes of modernity to produce an articulation of black authority always, already under threat for eradication or ridicule. Undeterred, nineteenth-century Haitian leaders mounted a century's-long battle to situate Haiti at the centre of the Atlantic world.